ETHNOSAINS DALAM PEMBELAJARAN IPA: MENANAMKAN KEBHINEKAAN GLOBAL MELALUI KEARIFAN LOKAL - Adellestia, Geby; Siwi, Dwi Anggraeni; Sari, Nurratri Kurnia; Sugiyanto, Y; Dana Elita, Mutiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education serves as a strategic means to shape the character and identity of a nation. In the era of rapid globalization and scientific advancement, Indonesia’s education system faces significant challenges, such as maintaining global diversity without neglecting the progress of science and technology. One relevant approach to addressing these challenges is integrating the values of Pancasila through the Pancasila Student Profile in the learning process, particularly in science subjects at the elementary school level. This study aims to describe the implementation of ethnoscience values in science (IPA) learning in elementary schools as a means of instilling global diversity through the reinforcement of local wisdom. This research employed a descriptive qualitative method with data collection techniques including observation, interviews with teachers and students, and document studies at elementary schools that integrate local culture into science learning. Data analysis involved data reduction, data presentation, and conclusion drawing. Data validity was ensured through technique triangulation and source triangulation. The results show that science learning based on ethnoscience can be integrated through contextual activities, one of which is the tie-dye batik-making activity at school. This activity not only enhances students’ scientific understanding but also instills values of diversity such as appreciation for local cultural heritage, collaboration, and openness to differences. Thus, ethnoscience based on local wisdom has the potential to strengthen students’ local identity while also shaping the character of global citizens who value diversity.